Pengaruh Tanaman di Dalam Kelas Studio Perancangan Arsitektur untuk Mengurangi Sick Building Syndrome Mahasiswa - Chairiyah, Riri (Universitas Aisyiyah Yogyakarta, 2024)
: Architecture learning activities are predominantly carried out indoors. Architecture students typically spend 2–4 hours inside the studio working on design assignments, which involve translating design concepts into visual media, either in 2D or 3D formats. This prolonged use of indoor space creates a demand for environments that meet comfort standards to ensure students’ health and well-being during learning activities. Plants are recognized as supporting elements in improving indoor air quality. However, their role in reducing student complaints related to Sick Building Syndrome (SBS) within architecture studio spaces has not yet been widely studied. Addressing this gap is important for enhancing the quality of student learning. This study was conducted in an Architectural Design Studio classroom under two controlled conditions: with indoor plants and without indoor plants. A total of 49 students participated by completing questionnaires, while indoor air quality (IAQ) measurements were also carried out to establish a baseline for changes attributable to the presence of plants. The findings revealed that the presence of indoor plants not only improved air quality but also enhanced concentration, comfort, and perceived health among users of the space. Notably, the addition of plants equivalent to just 1% of the studio’s floor area was associated with up to a 25% reduction in reported Sick Building Syndrome complaints.